Cholecystokinin type B receptor antagonist PD-136, 450 is a partial secretory agonist in the stomach and a full agonist in the pancreas of the rat. Issue 2 (February 1994) - Schmassmann, A; Garner, A; Flogerzi, B; Hasan, M Y; Sanner, M; Varga, L; Halter, F
Abstract : Gastrin (cholecystokinin type B (CCK-B)) receptor antagonists may help to elucidate the physiological role of gastrin, have therapeutic potential as acid antisecretory drugs, and may be of use as adjuvant therapy for gastrin sensitive tumours. In binding studies, the gastrin receptor antagonist PD-136, 450 had at least 1000 fold greater affinity for gastrin (CCK-B) than CCK-A receptors. In this study the biological activity of PD-136, 450 was evaluated in conscious and anaesthetised rats. PD-136, 450 antagonised gastrin stimulated acid secretion after subcutaneous (IC50: 0.28 mumol/kg; conscious rats) and intravenous (IC50: 0.17 mumol/kg; anaesthetised rats) administration. In basal secreting fistula animals, the compound stimulated acid output to 30 (5)% of the maximal response to gastrin. Stimulant activity was not caused by gastrin release. As an agonist PD-136, 450 was about 350 times less potent than gastrin-17 on a molar basis. In addition, PD-136, 450 was a powerful agonist of pancreatic secretion in anaesthetised rats. The specific gastrin antagonist L-365, 260 inhibited the (partial) agonist activity of PD-136, 450 in the stomach and the specific CCK-A receptor antagonist L-364, 718 inhibited the agonist activity of PD-136, 450 in the pancreas. It is concluded that the agonist effect of PD-136, 450 is mediated via interaction with the gastrin (CCK-B) receptor in the stomach and the CCK-A receptor in the pancreas.